The Antioxidant and Anti-Inflammatory Effects of Quercus brantii Extract on TNBS-Induced Ulcerative Colitis in Rats. (7th January 2021) - Alizade Naini, Mahvash; Mehrvarzi, Shayan; Zargari-Samadnejadi, Asal; Tanideh, Nader; Ghorbani, Mohammad; Dehghanian, Amirreza; Hasanzarrini, Maryam; Banaee, Farnaz; Koohi-Hosseinabadi, Omid; Irajie, Cambyz; Iraji, Aida
Abstract : Objectives . Ulcerative colitis is a common subtype of persistent inflammatory bowel disease with high morbidity consequences. Despite unknown definite pathogenesis, multiple anti-inflammatory medications are used for its treatment. Traditionally, Quercus brantii (QB), mostly available in the Middle East, has been used for gastrointestinal disorders. Other beneficial effects associated with QB include reduction of oxidative stress, inflammations, homeostatic instability, and improvement in clinical conditions. Materials and Methods . This experimental study was designed to assess the possible therapeutic effects of QB on UC and compare its effects with those of sulfasalazine. Of the 70 Wistar rats clustered in seven groups, ten received only alcohols and sixty were confirmed to be suffering from trinitrobenzene sulfonic acid- (TNBS-) induced colitis. Four groups received different dosages of QB extract via oral and rectal routes, one received sulfasalazine, and the other remaining two groups received nothing. The effects of QB were evaluated by assessing macroscopic and histologic scoring, measuring inflammatory mediators, and determining oxidative stress markers. Results . Comparing to the untreated TNBS-induced control groups, QB-treated groups showed a dose- and route-dependent improvement comparable with sulfasalazine. Treating rats with QB reduced the microscopic and macroscopic damage, decreased TNF- α, IL-6, NO, MPO activity, and MDA content, increased superoxide dismutase (SOD) activity, and reduced body weight loss. Conclusions . Our data recommended the anti-inflammatory and antioxidant effects of QB extract in a dose-dependent manner.